2002
DOI: 10.1074/jbc.m110417200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of CAPER, a Novel Coactivator of Activating Protein-1 and Estrogen Receptors

Abstract: Transcriptional coactivators either bridge transcription factors and the components of the basal transcription apparatus and/or remodel the chromatin structures. We isolated a novel nuclear protein based on its interaction with the recently described general coactivator activating signal cointegrator-2 (ASC-2). This protein CAPER (for coactivator of activating protein-1 (AP-1) and estrogen receptors (ERs)) selectively bound, among the many transcription factors we tested, the AP-1 component c-Jun and the estra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
126
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(131 citation statements)
references
References 43 publications
5
126
0
Order By: Relevance
“…19 CAPER is identical to the human protein HCC1.4, which was previously described as a novel nuclear autoantigen in human hepatocarcinoma. 19,21 CAPER was also shown to be related to known splicing factors such as the U2 auxiliary factor (U2AF65) and the poly(U)-binding-splicing factor-60 (PUF60).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…19 CAPER is identical to the human protein HCC1.4, which was previously described as a novel nuclear autoantigen in human hepatocarcinoma. 19,21 CAPER was also shown to be related to known splicing factors such as the U2 auxiliary factor (U2AF65) and the poly(U)-binding-splicing factor-60 (PUF60).…”
Section: Discussionmentioning
confidence: 92%
“…19 Using glutathione-S-transferase (GST)-pulldown and luciferase reporter assays, Jung et al (2002) demonstrated that CAPER directly interacted with ERα/β and c-Jun and potently stimulated their transcriptional activity in vitro. 19 However, the role of CAPER in human breast cancer pathogenesis remained unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2F; Loerch et al 2014). These three proteins function in alternative splicing (Page-McCaw et al 1999;Lallena et al 2002;Dowhan et al 2005;Hastings et al 2007;Huang et al 2012); PUF60 and CAPERα also are coactivators of transcription (Liu et al 2000(Liu et al , 2001Jung et al 2002;Dowhan et al 2005;Dutta et al 2008). Other UHM-containing proteins participate in related pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to CBP, NRC has been reported to associate with a number of other factors, including CoAA, PIMT, CAPER, and NIF-1 (27,28,40,71). Unlike NIF-1, CAPER, PIMT, and CoAA each contain RNA binding motifs.…”
mentioning
confidence: 99%